ADEQUACY ANALYSIS OF WASTE TRANSPORTATION FACILITY WITH CYCLIC SCHEDULING, CASE STUDY: CIREBON DISTRICT - Fathimatuzzahroh, Evi
The increase of Indonesia’s population density has had an impact to many aspects of life and the environment. One of the environment problems that are not easily handled is the waste problem. Cirebon Regency as one of the regions of Indonesia with a high population density has doubled the volume of waste produced per person / day in 4 years (2012-2016). On the other hand, with limited government resource and funding, the existing waste management cannot cope with the increasing amount of waste from the community. It is indicated with the overloading waste in temporary disposal sites and already overflowing into the nearby streets. The objective in this study is to construct a simple mathematical model for waste collection and transportation from the temporary disposal sites to the landfill sites. A waste transportation scenario is chosen to simulate the real condition in the field. The result is represented in a formulation relating the number of trucks, the daily supply of waste and the maximum of days in which no overflow of waste during that period.